Analisis Ide Kreatif Kristiadi Sebagai Sutradara Obrolan Angkring Episode Gara-Gara Facebook TVRI Yogyakarta - -, NRA. Candra DA; Suksmamurti, Bhayu (Seni Media Rekam ISI Surakarta, 2014)
This study focuses on observations on aspects of creative ideas. This study basically aims to uncover how creativity of Kristiadi as director formed and how the manifestation of creativity is present. This study is a qualitative research, the data obtained through interviews, direct observation, and accompanied by review of literature that are directly related to the theme of the study. Results of subsequent data processing presented descriptively, while the method of analysis performed by the data collection and then classify it, and then analyze it based on the theoretical foundation used. The study concluded, first that packaging program â€œObrolan Angkringâ€ is framed by creative ideas of Kristiadi, that is, thematic comedians initiated by Kristiadi make this program has the feel of humor that is able to entertain or the function of television includes three areas of information, entertainment and education can be expressed. Second, creative ideas of Kristiadi in the program â€œObrolan Angkringâ€ is influenced by five factors include (1) the presence of ideas, (2) creative consciousness, (3) awareness of communication, (4) social intelligence that generate awareness of the social institutions and (5) capability which produces the television media. Through these five factors makes the notion of â€œGara-gara Facebookâ€ as the theme of media offerings can be presented and produced. The process of realizing the idea in the form of display programs conducted through the stages of preproduction, production and postproduction. Thus through creative ideas, Kristiadi is able to improve the quality of the broadcast program, so it can also have an impact on the growing public interest in the program â€œObrolan Angkringâ€ produced by the station TVRI Yogyakarta. Keywords:Â idea, creative, Obrolan Angkring, TVRI Yogyakarta